A Deep Dive into the Botanical and Medicinal Heritage of Taxus - Alex-Robert Jîjie; Dan Iliescu; Laura Sbârcea; Casiana Boru; Dalia Pătrașcu; Oana Andrada Iftode; Ionela-Daliana Minda; Ștefana Avram; Cristina-Maria Trandafirescu; Cristina Adriana Dehelean; Elena-Alina Moacă (Plants)
The genus Taxus comprises a unique group of gymnosperms known for their botanical longevity, cultural significance, and exceptional pharmacological potential. This review explores the multifaceted profile of Taxus species, with a focus on their morphological traits, phytochemical composition, traditional uses, and therapeutic applications. Particular attention is given to taxanes, especially paclitaxel, which have revolutionized cancer treatment through microtubule-stabilizing mechanisms. In addition to well-established uses of the bark and leaves, the review synthesizes emerging research on the aril, a non-toxic and antioxidant-rich plant part, suggesting novel biomedical applications. By integrating ethnobotanical knowledge with contemporary pharmacological insights, this work underscores the enduring relevance of Taxus in traditional medicine while emphasizing its evolving role in modern drug discovery. The findings advocate for intensified interdisciplinary research and sustainable exploitation strategies to fully harness the genus’s therapeutic potential without compromising biodiversity.